Fine mapping of MRT9 locus through genome wide homozygosity mapping in a consanguineous Pakistani family - Shoaib Ur Rehman; Shahid Mahmood Baig; Larse Hasen; Ilyas Ahmad; Rahmat Ali; Masroor Hussain (Journal of the Pakistan Medical Association, 2019)
Intellectual disability (ID) or Mental Retardation (MR) is a broad term, which occupies several medical directions. It is extremely heterogeneous and has about reported 25,000 genes of which half of the genes expression have been found in the brain. Intellectual disability causes severe disability and has a worldwide prevalence of around 2% while autosomal recessive form of ID causes almost 25% of all non syndromic (NS) ID cases. A consanguineous family (who will be referred as) MR7 with phenotype of ID was sampled in Swat region of Pakistan.All affected individuals in the family were observed having a low IQ and cognitive mutilation with no sign of biochemical, skeletal or neurological abnormalities. Continou....